ANALISIS POTENSI WILAYAH BERBASIS KOMODITI PERTANIAN DI KABUPATEN BONE BOLANGO - Paramata, Sri Hantuti; Rahman, Yustin (Universitas Muhammadiyah Gorontalo, 2024)
The potential of an area is important to identify, especially potentials that have cooperative and competitive advantages to encourage economic growth. This study aims to analyze the potential of agricultural commodity-based areas in Bone Bolango Regency. The approach taken to conduct research using a qualitative approach. The data source used is the time series data of Brutto Regional Domestic Products for the last five years (2017-2021). The results of the study concluded that the development of agricultural commodity-based areas has not been maximized to encourage the growth and development of the Bone Bolango Regency area in the 2017-2021 period. Based on the analysis using the Location Question (LQ) shows that on average in the period 2017-2021 the LQ value of the agricultural sector is less than one (0.95). This value means that the commodity of agricultural products consisting of the food crop sub-sector, the fishery sub-sector, the plantation sub-sector, and the forestry sub-sector is not yet a base commodity, and is only categorized as a non-base sector